1864 Mont. Laws 355, § 1 [Deadly weapons] - (:unkn) unknown (General Publisher, 1865)
Prohibited the concealed carry of any pistol, Bowie-knife, dagger, or other deadly weapon. Violators fined not less than twenty-five but no more than one hundred dollars.
--
Keywords: CARRY - CONCEALED